Correction of renal tubular acidosis in carbonic anhydrase II-deficient mice with gene therapy. - Lai, L W (1998)
Carbonic anhydrase II (CAII) deficiency in humans is associated with a syndrome of renal tubular acidosis, osteopetrosis, and cerebral calcification. A strain of mice of CAII deficiency due to a point mutation also manifests renal tubular acidosis. We report here that retrograde injection of cationic liposome complexed with a CAII chimeric gene, using a cytomegalovirus (CMV) promoter/enhancer as an expression cassette to drive human CAII cDNA, into the renal pelvis of CAII-deficient mice results in expression of CAII in the kidney. The levels of both the CAII gene and its corresponding mRNA were highest by day 3 after treatment, diminishing thereafter, but remaining detectable by 1 mo. After gene therapy, CAII-deficient mice restored the ability to acidify urine after oral administration of ammonium chloride. The ability to acidify urine was maintained at 3 wk after gene therapy, and was eventually lost by 6 wk. Immunohistochemistry studies using anti-CAII antibodies showed that CAII was expressed in tubular cells of the outer medulla and corticomedullary junction. The gene therapy was not associated with nephrotoxicity as assessed by blood urea nitrogen levels and renal histology. To our knowledge, this is the first successful gene therapy of a genetic renal disease. Our results demonstrate the potential of gene therapy as a novel treatment for hereditary renal tubular defects.